Comparison of Sense of Humor and Burnout in Surgeons and Internal Medicine Physicians. Issue 11 (November 2022) - Paran, Maya; Sover, Arie; Dudkiewicz, Mickey; Hochman, Ohad; Goltsman, Galina; Chen, Yaakov; Zilber, Karina; Merin, Offer; Aranovich, David; Kessel, Boris
Abstract : Sense of humor can help remove interpersonal barriers, has a positive physiological positive effect, and may reduce mortality. Burnout is common among physicians and has been reported to be associated with reduced workplace burnout. This study aimed to evaluate humor styles in surgeons and internal medicine physicians and investigate the association between sense of humor and burnout among these physicians. Abstract: Objectives: We aimed to evaluate humor styles in surgeons and internists and investigate the association between humor and burnout. Methods: A cross-sectional survey of physicians in surgical and medicine departments was conducted, assessing sense of humor and burnout using the Humor Styles Questionnaire and the Emotional Exhaustion subscale of the Maslach Burnout Inventory-Human Services Survey for Medical Personnel. Results: For 131 surgeons and 72 internists, no differences in humor styles were found. A sense of personal accomplishment was more common among surgeons ( P = 0.03) and rates of burnout were lower for surgeons ( P = 0.02). Physicians with a higher-than-average score in affiliative and self-enhancing humor were less likely to suffer from burnout ( P < 0.0001 and P = 0.03, respectively). Conclusions: Surgeons and internists have similar styles of humor. Surgeons suffer less from burnout. Affiliative and self-enhancing humor styles are associated with reduced burnout.